Blood parameters of migratory shorebirds at Peninsula Valdes, Patagonia - D'amico, Veronica Laura; Hevia, Glenda Denise; Bertellotti, Néstor Marcelo (Wader Study)
We present blood parameters related to body condition and immune function of three shorebird species Calidris canutus rufa, Calidris fuscicollis and Charadrius falklandicus at a feeding site in Peninsula Valdés, Patagonia, Argentina, during their non-breeding season. We determined concentrations of glucose, cholesterol, and triglycerides, the leukocyte profile and the heterophil/lymphocyte ratio. These data constitute the first report of these blood parameters in shorebirds at this location. These data provide baseline information for ecological studies on these species in this area. The data could also be used in larger meta-analyses comparing blood parameters across geographical areas, different species and over time. Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Hevia, Glenda Denise. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina Fil: Bertellotti, Néstor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Centro Nacional Patagónico. Centro para el Estudio de Sistemas Marinos; Argentina